Refined Analysis of a Cross-Sectional Doping Survey Among Recreational Triathletes: Support for the Nutritional Supplement Gateway Hypothesis - Heller, Sebastian; Ulrich, Rolf; Simon, Perikles; Dietz, Pavel (Frontiers in Psychology, 2020)
Introduction: The current literature provides no consensus that nutritional supplements (NS) may provide a gateway to doping. Especially studies in recreational athletes are lacking. Within a previous cross-sectional empirical study, our group provided first evidence that the use of NS may provide a gateway for the use of doping substances in recreational triathletes. For the present paper, we refined the analysis of the triathletes’ survey in order to provide evidence for a nutritional supplement gateway hypothesis in recreational athletes. Methods: A self-report paper-and-pencil questionnaire was distributed to a sample of 2,997 competitive Ironman and Half-Ironman (n = 1,076; 36.1%) triathletes. The randomized response technique (RRT) was used to assess the 12-month prevalence estimate for the use of doping substances. The prevalence for the use of NS was assessed by using direct questioning. Two-tailed (α = 0.05) large-sample z-tests were performed to assess whether the estimated prevalence for the use of doping substances differs significantly between users and non-users of NS. Results: The 12-month prevalence estimate for the use of doping substances was significantly higher in athletes who reported to use NS (20.6%) compared to those who did not (11.4%; z = 2.595, p = 0.0097). Conclusion: The present results are consistent with the hypothesis that the use of NS provides a gateway to the use of doping substances. Therefore, doping prevention concepts should not primarily focus on preventing the use of doping substances per se, but should start one step earlier, namely by the use of NS.